(untitled) (Research, Society and Development, 2020)
One of the three main problems facing the Indonesian people in the midst of the current swift of globalization and information is the problem of radicalism, intolerance and the crisis of national identity. The reason as written in the national development agenda is because the politics of uniformity has eroded the character of Indonesia as a warrior nation, fading solidarity and mutual cooperation, and marginalizing local culture. This study aims to find out and explain Pancasila as the foundation and goals of Indonesia’s human development in the President Jokowi era. This study uses a qualitative-descriptive method with a literature review approach, by reviewing the 2014-2019 Medium-Term Development Plan (RPJMN) document which is the program implemented during one period of President Joko Widodo’s administration. The results showed that the values of Pancasila as the philosophy of life of the Indonesian people had not yet been fully manifested, both at the level of concepts and in the implementation of national development programs. However, efforts to increase Indonesian human development which more ’Pancasila’ have been included in the 2014-2019 RPJMN.